ANALYSIS OF INCOME AND EXPENDITURE BUDGET OF THE MUNICIPAL ADMINISTRATION TUKUY-MICHELSKEHO OF THE VILLAGE COUNCIL - Anna Savtsova; Olga Patsenko; Zukhra Yarykova (Вестник Северо-Кавказского федерального университета)
The local budget is the basis of each municipality, as to the adequacy or shortage of Finance affects the standard of living of the population and its social stability. In the article the definition of the local budget, revenues and expenditures, as well as the analysis of structure of incomes and expenditures of local budgets on the example of the municipal administration Tukuy-Mekteb of the village council.